KAJIAN KELAYAKAN PENGOLAHAN MEDIA TANAM ORGANIK PERUSAHAAN PERORANGAN “2 TIA AGRI” DI KALIMANTAN SELATAN - Husinsyah Husinsyah; Fitri Mahyudi (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2022)
This study aims to determine technically the implementation of organic growing media processing business on PO. 2 Tia Agri. To find out economically the large costs, revenues, profits and business feasibility of processing organic growing media on PO. 2 Tia Agri. In its implementation, the business of processing organic growing media on “PO. 2 Tia Agri” in Banyu Irang Village, Bati-Bati District, Tanah Laut Regency, South Kalimantan Province in general has been running well. Production activities consist of several main stages, namely material preparation, mixing all ingredients, fermentation process, packaging, and delivery. With a production capacity of 20 tons (20,000 kg) of organic growing media for 1 (one) production cycle with a selling price of Rp.1,000 per kg. The income obtained in one production of organic growing media processing business is an average of Rp. 20,000,000 and a total cost of Rp. 16,396,506,47 and the profit obtained in one production is Rp. 3,603,493.53. The RCR value of Organic Planting Media Processing Business is 1.22 so it is feasible to cultivate